Analysis Of Bias And Purity Indices In Packaged Cooking Oil And Bulk Cooking Oil Using The Diffraction Grid Method - Syifa Fauzia; Luma Alfiasti Sulton; Ayu Aulia Asyhari; Ahmad Suryadi; Fuji Hernawati Kusumah (Jurnal Multidisiplin Indonesia, 2023)
Cooking oil is a fundamental daily necessity, and both packaged and bulk oils are susceptible to structural changes and contamination that can influence the bias index. This research aims to analyze the purity of packaged and bulk cooking oil, investigate the relationship between the bias index and usage time, and identify factors influencing the bias index in both types of cooking oil using the diffraction grid method. The study revealed bias indices produced from packaged cooking oil before usage, after 10 minutes of usage, and after 15 minutes of usage, namely 5.08×108; 5.22×108 and 3.94×108, respectively. The bias indices from bulk cooking oil under the same conditions were 4.68×108; 3.61×108 and 3.37×108, respectively. Based on the research results, it is evident that packaged cooking oil exhibits a higher level of purity compared to bulk cooking oil. The relationship between the bias index and usage time is inversely proportional, indicating that the longer the cooking oil is used, the smaller the Refractive Index value becomes.